Biomineralogy of Angiogenesis - Pawlikowski, Maciej (Archives of Clinical and Biomedical Research, 2017)
Regeneration of blood vessels and their development occur in the damaged spots. This phenomenon suggests that the destruction process itself stimulates development of blood vessels and results in healing and self-repair of tissue. Learning about those self-repair processes is extremely important for restoring tissues and organs to their proper functioning in systems and the whole body. Therefore, recognizing the processes of angiogenesis appears to be the key in treating numerous diseases. Long-term research on blood vessels, their development and mineralization [1-9] as well as on mineralization and demineralization of bones and the process of bone healing [10-12] and the phenomena of tumor mineralization [9, 12-14] have supplied the author with numerous insights into angiogenesis. This publication is a summary of those insights.